WORKSHOP PELATIHAN PERANCANGAN INTERNET OF THINGS BERBASIS ARDUINO UNO JENIS R3/R3 SMD DI SMK SWASTA KARYA UTAMA KOTA TANJUNGBALAI - Ricki Ananda; Muhammad Amin (Jurdimas (Jurnal Pengabdian Kepada Masyarakat) Royal, 2019)
Abstract: Current technological developments are no stranger among students, almost all students now have an Android that is enabled to share information and be used to help with daily activities. Based on the usefulness of android which is only enabled to share information or as a communication tool, the service team creates training or workshops which later aims to develop students' interest in reviewing or developing technology in the field of android or in the controller field. In order for the training not to start from the ground up, the training participants were taken from the main works of private vocational schools, majoring in computers, class XI of the Department of Software Engineering (RPL), with a total number of participants of 53 people. The implementation of a two-day workshop found results, on the first day with the theme of training on IOT-based automatic switch hardware design, it was found that 46 students managed to assemble automatic hardware switches, and 7 students failed to assemble the hardware automatically perfectly. On the second day, 53 students succeeded in making an automatic software switch on Android, and during the trial, all students also managed to do it. From the two days of the workshop activities, and seen from the students' activeness and curiosity about the development of Android and the controller, many students still want to know, other developments from Android besides being used as automatic switches are based on IoT. Keyword: Royer Oscillator circuit, Power wireless transfer, Booster converter circuit  Abstrak: Perkembangan teknologi saat ini sudah tidak asing dikalangan pelajar, hampir semua pelajar kini memiliki android yang difungsikan untuk berbagi informasi serta difungsikan untuk membantu kegiatan sehari hari. Berdasarkan kegunaan android yang hanya difungsikan untuk berbagi informasi atau sebagai alat komunikasi, maka tim pengabdian membuat pelatihan atau workshop yang nantinya bertujuan untuk menumbuh kembangkan minat siswa siswi dalam mengulas atau mengembangkan teknologi dibidang android dibidang controller. Agar pelatihan tidak dimulai dari dasar, maka peserta pelatihan diambil dari SMK Swasta karya utama, jurusan komputer, kelas XI Jurusan Rekayasa Perangkat Lunak (RPL), dengan total peserta 53 orang. Terselenggaranya workshop selama dua hari,mendapati hasil, pada hari pertama dengan tema pelatihan perancangan hardware switch otomatis berbasis iot, didapati 46 siswa berhasil merangkai hardwarei switch otomatis, dan 7 siswa tidak berhasil merangkai hardware otomatis secara sempurna. Dihari kedua, 53 siswa berhasil membuat software switch otomatis di android, dan pada saat uji coba, seluruh siswa juga berhasil melakukannya. Dari dua hari kegiatan workshop yang dilakukan,dan dilihat dari keaktifan dan rasa ingin tahu siswa tentang pengembangan dari android dan controller, banyak siswa yang masih ingin tahu, pengembangan lain dari android selain digunakan sebagai switch otomatis berbasis iot. Kata Kunci: Royer Oscillator circuit, Power wireless transfer, Booster converter circuit